Human lymphotoxin mutein lacks hypotensive activity but has higher in vivo antitumor activity than lymphotoxin or tumor necrosis factor - Taniyama, Mitsue (The National Academy of Sciences of the USA, 1997)
A serious drawback of tumor necrosis factor α (TNF) as a clinical antitumor agent is that it also has hypotensive activity. To overcome this problem, derivatives of its sister cytokine lymphotoxin (TNF-β or LT) were prepared. One of them, mutein 2 (Mut2) has a deletion of amino acids 1–7 but contains substituted amino acids, Met-Phe-Pro at positions 8–10 of the mature human LT. This mutein has no hypotensive activity at the maximum dose (10 mg/kg) tested on rats. In contrast, a much lower dose (1 mg/kg) of TNF and LT caused a significant blood pressure drop. In vivo studies revealed that Mut2 was more effective than TNF or LT against MethA (a mouse tumor line) as judged by the therapeutic ratio [calculated as LD(50) (dose that kills 50% of the animals)/ED(50) (dose that reduces the tumor size by 50%)]. With five other different mouse tumors and two different human tumors, Mut2 was also effective and the effectiveness was comparable or superior to that of TNF or LT. These results suggest the possibility that this derivative may be usable as a clinical antitumor agent without the serious side effects associated with TNF.